Long-Term effects of physical activity on weight loss, metabolic parameters and blood pressure in subjects undergoing bariatric surgery : A 5-year follow-up study - Moriconi, Diego (Elsevier, 2025)
metabolic control in obesity, although over time there is a proportion of weight regain and type-2-diabetes (T2D) relapse.
Aims: to explore the role of physical activity (PA) after surgery and its impact on metabolic parameters during a 5-year follow-up.
Methods: 148 individuals who underwent bariatric surgery completed scheduled examinations over 5-years. Physical assessments and laboratory tests were conducted pre-surgery and annually thereafter. PA levels were evaluated using the International Physical Activity Questionnaire.
Results: participants were split into the PA group, who engaged in regular physical activity, and No-PA group, who remained sedentary throughout. In T2D individuals before surgery, PA group showed significant reductions in blood pressure and a lower T2D recurrence (6.7 ​% vs 36 ​%) compared to No-PA group. In normoglycemic individuals, the PA group led to sustained BMI reduction and improved blood pressure control (p ​< ​0.001) compared to No-PA group, for the entire duration of follow-up.
Conclusions: regular PA demonstrated cardio-metabolic benefits post-bariatric surgery. Integrating PA into post-bariatric care could enhance long-term outcomes.